1999
DOI: 10.1029/1999ja900286
|View full text |Cite
|
Sign up to set email alerts
|

Structure of disturbances in the dayside and nightside ionosphere during periods of negative interplanetary magnetic field Bz

Abstract: Abstract. By comparing data from a globally distributed set of high-latitude magnetic observatories with optical data in the nightside auroral ionosphere, we studied the features of short-term activations (_<10-15 min) during periods of steady magnetospheric convection (SMC) observed between two substorms. We found that the occurrence of local auroral and current structures stretched along the meridian to several hundreds of kilometers is the characteristic feature of activations in the nightside ionosphere. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 52 publications
(20 reference statements)
3
20
0
Order By: Relevance
“…In particular, streamers or NS Sun-aligned arcs which peel off the auroral oval and extend to the latitude of the main ionospheric trough will be investigated further using other AWFC events detected with TIGER. It is interesting to note that reported propagation speeds of NS Sun-aligned arcs (Solovyev et al, 1999) and Ps6 pulsations (Saito, 1978) are both comparable to the westward drift speeds measured during our AWFC.…”
Section: Discussionmentioning
confidence: 66%
“…In particular, streamers or NS Sun-aligned arcs which peel off the auroral oval and extend to the latitude of the main ionospheric trough will be investigated further using other AWFC events detected with TIGER. It is interesting to note that reported propagation speeds of NS Sun-aligned arcs (Solovyev et al, 1999) and Ps6 pulsations (Saito, 1978) are both comparable to the westward drift speeds measured during our AWFC.…”
Section: Discussionmentioning
confidence: 66%
“…omega bands) most often in the morning sector and sometimes in the midnight sector. Recently, several cases of similar optical phenomena have also been reported in the evening sector (Solovyev et al, 1999).…”
Section: Introductionmentioning
confidence: 91%
“…In the dayside magnetospheric plasma, the necessary pressure gradient driving the interchange instability may take place, for example: i) during the periodic magnetopause oscillation that could lead to the formation of the gap between the central plasma sheet and the low-latitude boundary layer, as is frequently seen in the DMSP data Meng, 1992, 1994); ii) during the periods of northward IMF B z , when the magnetosheath plasma penetrates into the dayside magnetosphere via the reconnection process (Song and Russell, 1992). These possibilities were previously discussed by Lyatsky and Sibeck (1997) and Kozlovsky et al (2003) in connection with the problem of the generation of different kinds of dayside auroras.…”
Section: Possible Scenario For Formation Of Omega Aurorasmentioning
confidence: 99%
“…But, during the BBAE the IMF Bz was almost negative, thus it has comparatively less influence on the auroral emission boundary movement during BBAE than the IMF By. Solovyev et al (1999) studied the substorm time (AE∼400 nT) nightside auroral oval during the southward IMF Bz and reported that pre-magnetic-midnight auroral structure shrink to the equatorward edge of the auroral oval, however post-magneticmidnight sectors formed the omega band auroral structure. We observe nearly similar saturation during the BBAE, where nightside auroral oval boundaries shrink to poleward during the substorm and southward IMF Bz in the post-midnight sectors and form some auroral emission pattern like an omega aurora band.…”
Section: Bouncing Boundary Auroral Emissions (Bbae)mentioning
confidence: 99%